Acabou-se o que era doce, quem comeu se regalou-se : uma análise do clítico se em João Pessoa na interface Sociolinguística - Mello, Fernanda Rosário de (2009)
The variation in the usage of reflexive pronouns in Portuguese is a subject which has been studied by many linguists. Most of these studies point to a general tendency for clitic deletion, as in Veado (1982), D Albuquerque (1988), Nunes (1995), Lima (2006) and others. If, on the one hand, there are dialects which support that tendency, on the other hand there are other regions of Brazil where this movement is quite the reverse: instead of being deleted, the usage of the clitic pronoun is maintained and even applied in other contexts. The semantic variations in the functions of the pronoun se seem to provide evidence of linguistic processes of change, from the original function of a reflexive clitic pronoun to the category of a verbal affix, through a grammaticalization process (Bybee, 2001; Bybee et alii, 1994; Hopper & Traugott, 1993 and others). As such, we focus on the list of reflexive pronouns, specifically the reflexive pronoun se, which in the speech community of João Pessoa seems to be stable, different from other regions of Brazil. The trajectory of this pronoun is assessed through a quantitative control of linguistic and social factors, observing the direction of the influences that may affect the patterns of such pronoun. For that, I use data from VALPB (Projeto Variação Linguística no Estado da Paraíba (Hora; Pedrosa, 2005)) interviews. The general hypothesis raised in this doctoral thesis is that the different patterns of se in diverse regions from Brazil show that the phenomenon in analysis presents different stages of a grammaticalization process. While in some dialects the process is more developed, in the speech of the community of João Pessoa it would be less developed, where its usage expands to a higher frequency. In this process, both linguistic and social factors seem to favor and/or inhibit the changes. The main consequence is the reanalysis suffered by this item, with a rearrangement of the borders between the constituents of the sentences, so that se turns to have its categorical status altered, from its clitic position to verbal affix.